Hermite–Hadamard-type inequalities for r-convex functions based on the use of Riemann–Liouville fractional integrals - Wang, J.; Deng, J.; Fečkan, M. (Український математичний журнал, 2013)
By using two fundamental fractional integral identities, we deduce some new Hermite–Hadamard-type inequalities for differentiable r-convex functions and twice-differentiable r-convex functions involving Riemann–Liouville fractional integrals. Iз використанням двох фундаментальних дробових iнтегральних тотожностей отримано новi нерiвностi типу Ермiта – Адамара для диференцiйовних r-опуклих функцiй та двiчi диференцiйовних r-опуклих функцiй, що мiстять дробовi iнтеграли Рiмана – Лiувiлля.